Does faster hopping frequency improve response time and kicking speed in taekwondo roundhouse kick? - Kim, Y.-K.; Jung, H.-J.; Joo, J.-Y. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to investigate the effect of rhythmic hopping frequency on the response time and kicking speeds in Taekwondo roundhouse kick. Eleven elementary and middle-school athletes voluntarily participated in this study. They performed five roundhouse kicks at three different hopping frequencies (normal, 15% faster than normal, and 15% slower than normal) and no hop condition. Results indicated that the 15% slower hopping frequency induced a significantly longer response time than the 15% faster frequency. The 15% faster frequency resulted in faster maximum kicking speed than normal frequency did, while there was no difference in contact kicking speed. Partially the faster hopping frequency would be beneficial to kicking performance.